2020
DOI: 10.6026/97320630016602
|View full text |Cite
|
Sign up to set email alerts
|

Description of microbial diversity associated with ticks Hyalomma dromedarii (Acari: Ixodidae) isolated from camels in Hail region (Saudi Arabia) using massive sequencing of 16S rDNA

Abstract: Ticks are blood feeder able to transmit a wide diversity of microbes including pathogens. Therefore, it is of our interest to detect the diversity of microorganisms residing within ticks using massive sequencing of 16S rDNA. In this study, 200 adult ticks were collected from healthy camels in two localities from Hail province (Saudi Arabia). The analysis showed high microbial diversity dominated by the two domains (Archaea and Bacteria) associated with Hyalomma dromedarii from both regions. Proteobacteria (61.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(28 reference statements)
4
4
2
Order By: Relevance
“…Camels were heavily infested (94.3%) with H. dromedarii compared to all animals and these results concurred with our previous studies in the UAE [12,39]. Hyalomma dromedarii is known to harbor a variety of microbes with some tick-borne bacterial [25,[40][41][42] and protozoan pathogens [25] in the MENA region, including the UAE. There was no difference in tick prevalence between male and female hosts with the exception of goats, where more females were infested compared to males.…”
Section: Discussionsupporting
confidence: 90%
“…Camels were heavily infested (94.3%) with H. dromedarii compared to all animals and these results concurred with our previous studies in the UAE [12,39]. Hyalomma dromedarii is known to harbor a variety of microbes with some tick-borne bacterial [25,[40][41][42] and protozoan pathogens [25] in the MENA region, including the UAE. There was no difference in tick prevalence between male and female hosts with the exception of goats, where more females were infested compared to males.…”
Section: Discussionsupporting
confidence: 90%
“…Firmicutes, Proteobacteria , and Actinobacteria were the abundant phyla found in the present dataset and notably, Firmicutes was the most abundant one in all months. These results were slightly different from previous studies that reported all three phyla; however, they found that Proteobacteria was the most abundant phylum ( 22 , 33 , 34 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Microbial infections are pervasive in animal and human populations in healthy ecosystems ( 32 ). A limited number of studies on the microbial community structure of H. dromedarii ( 22 , 33 35 ) pointed to complex microbial assemblages in dwelling ticks comprising endosymbionts, commensals, and pathogens. Because in the UAE H. dromedarii ticks exist in the desert ecosystem under harsh environmental conditions, especially the extreme summer heat and drought, we hypothesize that their microbial species composition has gone way off in terms of the types of typical taxa found in other tick species or H. dromedarii in temperate environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the UAE, the genus Francisella was previously reported in H. dromedarii collected from camels, with a high relative abundance of 99.1% [ 8 ]. In addition, almost similar results were reported from Saudi Arabia, where Francisella was found to be a dominant genus with an abundance of 94.4% [ 34 ] and 42.1% [ 35 ] in H. dromedarii . It has been shown that tick endosymbionts mostly belong to the genera Francisella, Rickettsia and Coxiella [ 36 ] and that they probably have mutualistic relationships with ticks possibly also modulate tick vector capacity by influencing tick-borne pathogens’ colonization and transmission to vertebrate hosts [ 9 , 37 ].…”
Section: Discussionsupporting
confidence: 82%